ijee 2022
DOI: 10.48165/ijee.2022.58416
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Social Media Addiction on Mental Health of Emerging Adults

Abstract: In today’s world, many of us rely on social media. Though each has its benefits spending too much time on social media can lead to many mental health issues. So the present study on the effect of social media addiction on mental health of emerging adults was conducted in Dharwad district of Karnataka state during the year 2020-21 to assess the social media addiction and its effect on mental health of emerging adults. One hundred and sixty students were selected randomly from arts and science degree colleges of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
2
0
1
Order By: Relevance
“…Literatür incelendiğinde sosyal medya kullanım süresinin artmasının çocuklarda minnettarlık düzeyinin (Maheux vd., 2021) ve yaşam coşkusunun (Shoshani ve Kor, 2022) düşmesine neden olduğu görülmüştür. Ayrıca çalışmalar uzun süre sosyal medyada vakit geçirmenin yüksek riskli davranışlarla ilişkili olduğu (Vente vd., 2020), ruh sağlığını olumsuz yönde etkilediğini (Yamini ve Pujar, 2022), bilişsel, dil ve sosyal-duygusal becerileri üzerinde olumsuz etkileri olduğu tespit edilmiştir (Schwarzer vd., 2021). Sonuç olarak yapılan araştırmada dijital oyun oynama süresi ve sosyal medya kullanım süresi arttıkça minnettarlık, yaşam coşkusu, iyimserlik, sebat ve toplam okulda pozitif yaşam düzeylerinin düştüğü görülmüştür.…”
Section: Discussionunclassified
“…Literatür incelendiğinde sosyal medya kullanım süresinin artmasının çocuklarda minnettarlık düzeyinin (Maheux vd., 2021) ve yaşam coşkusunun (Shoshani ve Kor, 2022) düşmesine neden olduğu görülmüştür. Ayrıca çalışmalar uzun süre sosyal medyada vakit geçirmenin yüksek riskli davranışlarla ilişkili olduğu (Vente vd., 2020), ruh sağlığını olumsuz yönde etkilediğini (Yamini ve Pujar, 2022), bilişsel, dil ve sosyal-duygusal becerileri üzerinde olumsuz etkileri olduğu tespit edilmiştir (Schwarzer vd., 2021). Sonuç olarak yapılan araştırmada dijital oyun oynama süresi ve sosyal medya kullanım süresi arttıkça minnettarlık, yaşam coşkusu, iyimserlik, sebat ve toplam okulda pozitif yaşam düzeylerinin düştüğü görülmüştür.…”
Section: Discussionunclassified
“…Higher social media addiction levels of individuals who have anxious/ambivalent attachments and who structure their self-worth in the approval domain can be explained in this way. This need of individuals who have few people they can communicate with and be close to within their social environment leads them to meet this need through social media (31). This in turn leads to an increase in the level of social media addiction as the use of social media increases.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that students utilized online tools for various needs, benefiting their overall learning, reading, and writing abilities. Yamini and Pujara (2022) [21] found that 49.30% of respondents had a high level of social media addiction, possibly influenced by widespread smartphone use and daily posting habits.…”
Section: (A) Profile Characteristics Of the Respondentsmentioning
confidence: 99%